Constitutional-Legal Responsibility Of The Executive Bodies Of The State Authorities To Society And Citizens (Global Scientific Review, 2024)
The article talks about the legal, including some constitutional and legal, aspects of the responsibility of State bodies to increase their responsibility to society and the subject of improvement in legislation related to the application of constitutional-legal measures of responsibility in the system of local state authorities and citizens ' self-government, at the same time, the rules of social